2005
DOI: 10.2106/jbjs.c.01714
|View full text |Cite
|
Sign up to set email alerts
|

Fractures Following Radiotherapy and Limb-Salvage Surgery for Lower Extremity Soft-Tissue Sarcomas

Abstract: Women more than fifty-five years of age who are managed with removal of a thigh sarcoma combined with radiation therapy have a higher risk of pathologic fracture. The frequency of pathologic fractures associated with higher doses (60 or 66 Gy) of radiation is significantly higher than that associated with lower doses (50 Gy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 24 publications
1
86
1
3
Order By: Relevance
“…In studies by Lin et al and Holt et al [4,20], female gender appeared predictive of femoral fracture. These results have not been confirmed by other groups [6] or by our results.…”
Section: Discussionmentioning
confidence: 92%
“…In studies by Lin et al and Holt et al [4,20], female gender appeared predictive of femoral fracture. These results have not been confirmed by other groups [6] or by our results.…”
Section: Discussionmentioning
confidence: 92%
“…Both the total radiation dose Radiotherapy and the volume of tissue exposed are smaller with preoperative rather than postoperative treatment [37•]. As a result, patients who have undergone preoperative irradiation have fewer long-term radiation effects, such as limb edema, fibrosis, and pathologic fracture of irradiated bone [39,40]. This translates into improved patient function in this group compared with patients who receive postoperative irradiation [39].…”
Section: Treatmentmentioning
confidence: 99%
“…Although the temporal sequence of cellular events believed directly responsible for allograft healing have been described [5,20], the specific means by which perioperative irradiation affects these biologic processes are not fully characterized. Our previous in vivo study [15] suggested decreased expression of BMP-2 protein and mRNA at the host-allograft interface after exposure to clinically relevant doses of irradiation may, in part, explain the higher incidence of allograft-related complications such as nonunion [15,25] and fracture [24]. Thus, the overarching goal of the current study was to determine if sustained local delivery of the rhBMP-2 gene from a polymeric delivery system would enhance allograft incorporation as measured radiographically and histologically despite the host's exposure to preoperative radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the radiographic evaluation of allograft healing was performed by a single board-certified radiologist and we therefore did not address interobserver variability in radiographic interpretation using the ISOLS scoring system. Although used as a neoadjuvant therapy for the treatment of musculoskeletal sarcoma before en bloc resection of the tumor, preoperative radiation negatively affects the temporal cascade of healing events resulting in impaired and delayed allograft incorporation [15,22,[24][25][26]. Our data confirmed the negative effects of 50 Gy irradiation administered presurgery to the host tissues on allograft incorporation both histologically and radiographically; however, we were unable to demonstrate any positive healing effect of the therapeutically delivered BMP-2 plasmid through a polymeric microcarrier in either the nonirradiated or irradiated tissue beds, thus disconfirming our initial hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation